Management Of Physiotherapy Programs In Skin Flap For Thumb : Case Report - Della Annisa Thalib; Umi Budi Rahayu; Nilam Nur Hamidah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Skin flap is a skin graft procedure that will repair damaged skin by removing the soft tissue underneath. Objective: to determine Physiotherapy management in the form of giving electro therapy (ultrasound and Infrared) and exercise. Methods: The research method includes a